ENHANCING GEOMETRICAL DIMENSIONING AND TOLERANCING PROFICIENCY: A PRACTICAL APPROACH TO TRAINING AND LEARNING (Proceedings of the International Conference on Future of Education, 2024)
Geometrical Dimensioning and Tolerancing (GD&T) is a complex and detailed system used to communicate the design and manufacturing requirements of a part. GD&T is essential for the manufacturing industry as it ensures that parts are manufactured to the required specifications, reduces manufacturing errors and improves quality, simplifies communication between designers, manufacturers, and quality control personnel. Many technical schools and universities do not provide comprehensive training on GD&T, leaving students with limited exposure to the subject. This can make it challenging to acquire the necessary skills and knowledge to become proficient in GD&T. GD&T requires practical application to gain proficiency, and it can be challenging to find opportunities to practice in a real-world setting. Learning Geometrical Dimensioning and Tolerancing (GD&T) merely on a theoretical basis is not sufficient to become proficient in it. GD&T is a system that requires practical application to gain proficiency. This paper provides a review of teaching method used in a practical session designed for GD&T training and learning at a private technical institution. The finding from the review process will be used to conceptualise an effective pedagogy for GD&T training and learning.
Keywords: Geometrical Dimensioning; Practical; Proficiency; Training and Learning